Effect of Project Based Learning Method on Knowledge and Learning Activity in Graduate School Students - Manggandhi, Yuyun; Pamungkasari, Eti Poncorini; Raharjo, Setyo Sri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: The Project Based Learning (PjBL) model is a learning model that can make students have expertise and can understand the learning process. This study aims to look at the application of Project Based Learning (PjBL) to increase student activity, to see the character values and results of student academic achievement in the KKPMT practice subject to achieve competence. Subjects and Method: RCT research was conducted at STIKes Mitra Husada Karanganyar. The sample consisted of 90 students, 48 students as the control class and 42 students as the experimental class. Student activity is assessed with an observation sheet. Student character is assessed by means of a questionnaire. The results of learning achievement using the posttest and pretest instruments. The mean knowledge scores in both groups were compared by independent t-test. Results: The knowledge score after the intervention in the project-based learning group (Mean= 71.81; SD= 8.35) was higher than that of the control group (Mean= 67.73; SD= 8.64), and was statistically significant (p= 0.026). Project-based learning is effective in increasing students' knowledge of ICD. The activity score after the intervention in the project-based learning group (Mean= 68.83; SD= 12.87) was the same as the control group (Mean= 68.27; SD= 11.53), but statistically not significant (p= 0.827). Conclusion: This study concluded that project-based learning was effective in increasing students' knowledge of ICD but project-based learning was not effective in increasing student activity in discussing ICD subjects. Keywords: Project Based Learning, student character, student activity, learning outcomes. Correspondence: Yuyun Manggandhi. Masters’ Program in Public Health, Universitas Sebelas maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: Manggandhi88@gmail.com. Mobile: 0821 3384 6808.